2013
DOI: 10.5014/ajot.2013.006031
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of Full-Time Wrist Splinting and Education in the Treatment of Carpal Tunnel Syndrome: A Randomized Controlled Trial

Abstract: This study investigated the effects of wearing a wrist support splint for 8 wk and receiving a formal education program on patients with carpal tunnel syndrome (CTS), as well as factors associated with patients' desire to seek surgical intervention. Participants were recruited from a hospital surgical wait list and randomly assigned to an intervention group (n = 30) or a control group (n = 24). Significant improvements in measures of symptom severity and functional status over the duration of the study appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 36 publications
0
36
0
11
Order By: Relevance
“…However, previous reviews have shown moderate evidence supporting the use of wrist splints in the treatment of CTS 11,30 . Furthermore, as noted by Roll and Hardison, a randomized and controlled trial was not included in any of these reviews 36,37 . A trial by Hall et al showed that the use of a wrist splint improved symptoms in CTS patients 37 .…”
Section: Wrist Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous reviews have shown moderate evidence supporting the use of wrist splints in the treatment of CTS 11,30 . Furthermore, as noted by Roll and Hardison, a randomized and controlled trial was not included in any of these reviews 36,37 . A trial by Hall et al showed that the use of a wrist splint improved symptoms in CTS patients 37 .…”
Section: Wrist Immobilizationmentioning
confidence: 99%
“…Furthermore, as noted by Roll and Hardison, a randomized and controlled trial was not included in any of these reviews 36,37 . A trial by Hall et al showed that the use of a wrist splint improved symptoms in CTS patients 37 . There was no support for the long-term use of wrist splints in a review by Page et al 38 .…”
Section: Wrist Immobilizationmentioning
confidence: 99%
“…The authors based their recommendation on a small randomizedcontrolled trial comparing wrist splints and an educational program and a control group who received nothing. 2 Perhaps not surprisingly, the control group experienced a dropout rate of over 22% compared to 3% in the treatment group. This obviously places the internal (and therefore external) validity in question.…”
Section: What About Steroids?mentioning
confidence: 99%
“…[1][2][3][4][5] Lowquality studies do not adequately assess sodium intake, they use extreme variation in dietary sodium and they measure outcomes over a duration of a few days. They do not address known confounding factors for the outcomes being tested nor do they control for blood pressure (the main mechanism of sodium-induced harm) and they are conducted in populations with diseases where reverse causality is likely.…”
Section: Too Much Focus On Lowquality Science?mentioning
confidence: 99%
See 1 more Smart Citation